Katie's Canon : Womanism and the Soul of the Black Community, Revised and Expanded 25th Anniversary Edition - Cannon, Katie G. (Book collections on Project MUSE., 2021)
Over the years, Katie Cannon's students referred to her work in progress as ""Katie's canon."" Not only does this book represent the canon of Cannon's best work; the book itself directly addresses the issues of canon formation and canon reformation. Cannon canonizes a literary tradition and directly addresses both oppression and liberation of African American women. Now in an expanded 25th-anniversary edition, Katie's Canon still packs firepower.